Modeling the formation of an industrial enterprise operating income - Myznikova T.N.; Bunova E.V.; Yaroslavova E.N. (SHS Web of Conferences, 2017)
The developed economic and mathematical model of the industrial enterprise’s operating income formation allows to reveal cause-and-effect relations and to form a mechanism of influence of initial (base) indicators on the studied index (operating income of a business entity). The model is based on the regression analysis. The base indicators forming the economic and mathematical model are grouped into two blocks: production assets and labour resources influencing the enterprise’s financial standing, namely, its operating income. This grouping allows to evaluate efficiency of the influence of production assets and labour resources on the enterprise’s potential at taking of justified management decisions. The mechanism of the enterprise’s industrial potential management modeling includes analysis of base indicators (factors) of each of the considered blocks. With the help of the developed economic and mathematical model, by setting base values of factors, we can consider their influence on the resulting index — operating income of any business entity; and vice versa, by setting the resulting index we can analyze the influence of base indices for efficient management of the industrial enterprise’s operating income.